Magnetic field induced polarization enhancement in monolayers of tungsten dichalcogenides: effects of temperature. (27th November 2017) - Smoleński, T; Kazimierczuk, T; Goryca, M; Molas, M R; Nogajewski, K; Faugeras, C; Potemski, M; Kossacki, P
Abstract: Optical orientation of localized/bound excitons is shown to be effectively enhanced by the application of magnetic fields as low as 20 mT in monolayer WS2 . At low temperatures, the evolution of the polarization degree of different emission lines of monolayer WS2 with increasing magnetic fields is analyzed and compared to similar results obtained on a WSe2 monolayer. We study the temperature dependence of this effect up to T = 60 K for both materials, focusing on the dynamics of the valley pseudospin relaxation. A rate equation model is used to analyze our data and from the analysis of the width of the polarization dip in magnetic field we conclude that the competition between the dark exciton pseudospin relaxation and the decay of the dark exciton population into the localized states are rather different in these two materials which are representative of the two extreme cases for the ratio of relaxation rate and depolarization rate.